Benchmarking and performance measurement of supply chain management practices: a survey of Indian organisations. (12th July 2006) - Singh, Amar; Narain, Rakesh; Yadav, R.C.
Supply Chain Management (SCM) is regarded as a means of improving organisational effectiveness and for better realisation of organisational goals. Organisations now recognise the strategic contribution of suppliers to total performance and increasingly expect their suppliers to offer cost, quality, time, flexibility, delivery and technological advantages. This requires an efficient and effective supply chain to be developed. The supply chain needs to be continuously assessed for its performance and its activities benchmarked with respect to highest standards. While performance measurement helps management in providing feedback, assisting in diagnosing problems, revising organisations goals, reengineering business process etc., benchmarking provides benefits in process improvement, culture and financial gains etc. This paper is based on the data collected from a survey of 54 Indian manufacturing organisations carried out to ascertain issues related to benchmarking and performance measurement of SCM practices. The findings indicate that Indian organisations are using benchmarking mainly as a strategic tool for continuous improvement. The types of benchmarking used, important requirements for the success of benchmarking, criteria for suppliers' evaluation, improvements recorded in operational areas due to effective selection of suppliers and some useful index, which can be used for performance measurement of supply chain are also discussed.